Implikasi Hukum Pembayaran Dividen atas Saham yang Disita dalam Kasus Korupsi - Marbun, Yudha Cristovany (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2025)
Purpose: This study aims to examine the knowledge and understanding of the implementation of the tax system, including the quality of tax services provided by authorities, and to evaluate various factors influencing taxpayer compliance in Indonesia. Methodology: This study uses a juridical and sociological legal approach, applying descriptive-analytical methods. Data were collected from the literature and relevant sources and then analyzed qualitatively by organizing the information into coherent narratives to draw conclusions. Results: Low tax compliance is influenced by several factors, including limited public knowledge of tax regulations, low financial literacy, insufficient public awareness campaigns, and underutilized benefits of modernized tax services. Taxpayers are often unaware of the incentives offered for compliance. Additionally, cultural variables, such as the perception of tax obligations as communal idealsshaped by justice and social responsibility, play a role. However, there is still resistance due to unfamiliarity with online administrative procedures. Conclusion: Voluntary tax compliance improves when tax policies are perceived as fair and the benefits of paying taxes are recognized. Ethical and environmental elements, particularly those embedded in Indonesia’s communal culture, significantly influence taxpayer behavior. Although legal enforcement can increase compliance, social norms have a limited impact on actual tax practices. Ultimately, tax compliance directly supports national development and the public welfare. Limitations: This qualitative study may reflect some degree of subjectivity, and its findings are not generalizable. Citations are included to minimize bias. Contribution: This study suggests simplifying tax return terminology, utilizing free tools for profiling and monitoring taxpayer behavior, and improving outreach through Business Development Services (BDS) to enhance public understanding and compliance.